1983
DOI: 10.1111/j.1943-278x.1983.tb00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Hostility in Self‐Mutilation

Abstract: The presence of depression and hostility among self-mutilating patients is investigated. Mutilators, depressives and controls comprised the research samples. Non-significant differences in intropunitive hostility and depression were found between the clinical groups. Specific item differences in the depression assessment indicated a definite qualitative rather than quantitative difference in depressive symptomatology between the clinical groups. The interaction between hostility and depression and the implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
2

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 49 publications
2
40
0
2
Order By: Relevance
“…Again, the fact that we found less aggressive behaviour in our patients can be due to the fact that our results are based on a self-report questionnaire, in which social desirability can play a distorting role. Furthermore, we found-in the same way as Bennum (1983)-that selfinjurious patients show a stronger degree of self-abasement and selfcriticism, including guilt and self-punitiveness, than patients without SIB. From these findings one may conclude that SIB patients turn their anger against themselves (and not against others) because of guilt feelings and self-punitiveness as is often described in the literature (Simeon & Hollander, 2001).…”
Section: Discussionmentioning
confidence: 50%
“…Again, the fact that we found less aggressive behaviour in our patients can be due to the fact that our results are based on a self-report questionnaire, in which social desirability can play a distorting role. Furthermore, we found-in the same way as Bennum (1983)-that selfinjurious patients show a stronger degree of self-abasement and selfcriticism, including guilt and self-punitiveness, than patients without SIB. From these findings one may conclude that SIB patients turn their anger against themselves (and not against others) because of guilt feelings and self-punitiveness as is often described in the literature (Simeon & Hollander, 2001).…”
Section: Discussionmentioning
confidence: 50%
“…Whilst burning self is not a majority behaviour (occurring in 44% of incidents), it is interesting to note that it is most common type of self-harm amongst this sample of firesetters. Also the commonly occurring item, anger at others, is about twice as prevalent to the rates that have been reported in previous studies (Gardner and Gardner, 1975;Roy, 1978;Bennum, 1983). It is evident that there are some items, characteristic of most incidents that are common to fire-setting and self-harm: depression, physical aggression and verbal aggression.…”
Section: Frequencies Of Self-harm Itemsmentioning
confidence: 56%
“…Research has found that 10-32% of self-harmers report anger towards others leading up to acts of self-harm (Gardner and Gardner, 1975;Roy, 1978;Bennum, 1983). Simpson (1976) draws attention to the association between poor verbal ability, particularly with difficulties expressing needs and emotions, and self-harm.…”
Section: Conservative Modementioning
confidence: 99%
“…(Nö rop si ki yat ri Ar fli vi 2014; 51: [40][41][42][43][44][45] Anah tar ke li me ler: Hükümlü ve tutuklular, boyun eğici davranışlar, depresyon, intihar olasılığı çıkar çatışması: Yazarlar bu makale ile ilgili olarak herhangi bir çıkar çatışması bildirmemişlerdir. …”
unclassified